Comparison of blood flow analysis in stenosed and stented carotid artery bifurcation models. Issue 1 (31st December 2023) - Hameed, M. Saqib; Shah, Awais Ahmad; Khan, Muhammad Irfan; Ali, Awais; Hussain, Imtiaz; Bukhari, Muhammad Dawood
Abstract: Cardiovascular diseases have been a leading cause of death for the past several decades. A comparison of blood flow patterns through diseased and treated arteries can be beneficial in diagnosis and treatment. The computational fluid dynamic (CFD) analysis was utilized to numerically simulate the blood flow dynamics of stenosed and stented carotid artery bifurcation. Two lumen models were generated: first with the stenosis and then a stent was introduced to remove the abnormality. The control volume method was implemented to discretize the blood domain, and then the steady-state velocity inlet was used based on the measured blood flow rate. The transitional flow was observed in the post-stenotic region due to the high Reynold's number near peak systole; however, the flow exhibited laminar characteristics at the peak diastole. Four distinct locations downstream of the stenosis were used to compare the results. The internal carotid artery (ICA) stenosis resulted in high wall shear stresses, irregular flow patterns, and low-pressure areas. The velocity and pressure profiles oscillated in the immediate vicinity downstream of the stenosis. The stented model showed minimal pressure and velocity fluctuations, as well as minimal wall shear stresses. Additionally, for the stented model, the flow could not enter the transitional regime under both conditions. The proposed simulation methodology can be utilized until the abnormalities in the carotid artery geometry are removed and normal blood flow characteristics are achieved, which then become the basis for an optimal design of a carotid artery stent.